Economic sustainability in Ethiopia - Yohannes Girma; Abera Ayalew; Ewunetu Tazebew (Discover Sustainability)
Abstract This study focuses on examining the determinants of sustainable development by focusing the experience from Ethiopia. A time series analysis that covers the period from 1974 to 2023 was used for the analysis. It is designed to examine sustainability in its holistic view which is many previous studies failed to consider. Autoregressive integrated moving average model was used for the analysis. Dickey fuller test for stationarity and interpolation was used during the pre-estimation process. Principal component analysis was applied to develop index for the variable governance. The result showed that foreign direct investment, economic growth, carbon emission, tax revenue, external debt stock, inflation and governance have a significant effect on sustainable development. Residual test for the white noise and within sample forecast was used to validate the model. The 10 years forecast (2024–2033) showed that there is an increasing trend in sustainable development in Ethiopia due to increase in governance quality and economic growth. Thus, a coordinated policy framework that balances economic, environmental, and governance objectives is vital for Ethiopia’s sustainable future.